2021
DOI: 10.31234/osf.io/r9y3t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trust in Artificial Intelligence: Comparing trust processes between human and automated trustees in light of unfair bias

Abstract: Introducing automated systems based on artificial intelligence and machine learning for ethically sensitive decision tasks requires investigating of trust processes in relation to such tasks. In an example of such a task (personnel selection), this study investigates trustworthiness, trust, and reliance in light of a trust violation relating to ethical standards and a trust repair intervention. Specifically, participants evaluated applicant preselection outcomes by either a human or an automated system across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Of note, system reliability is only relevant in association with the other dimensions of AI, indicating that the mere mentioning, that AI is reliable does not improve assessment quality perceptions. Potentially, this may be due to a lack of information on the functioning of the different AI methods in this study (see Langer et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, system reliability is only relevant in association with the other dimensions of AI, indicating that the mere mentioning, that AI is reliable does not improve assessment quality perceptions. Potentially, this may be due to a lack of information on the functioning of the different AI methods in this study (see Langer et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, we analyzed participants’ trustworthiness and subsequent behaviors (i.e., scoring and ranking application forms) after being exposed to recommendations. To enhance ecological validity of our results, we selected a sample of experienced professionals involved in the recruitment process, in contrast with previous research on trust in selection context, in which participants involved were mainly students or working adults ( Diab et al, 2011 ; Dietvorst et al, 2015 ; Dietvorst, 2016 ; Lee, 2018 ; Langer et al, 2021a ) and only a few studies used participants actually involved in recruitment tasks in their organization ( Oberst et al, 2020 ). We selected participants from an online panel owned by a specialized company, Panelabs, which gives access to a panel that contains 500,000 French participants and provides a high level of quality control.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies revealed a tendency to disuse automation and highlight an aversion behavior. For example, Langer et al (2021a) concluded that participants in a personnel selection context perceived the human trustee as more trustworthy than an automated trustee. The authors explained these results by noting that human ability is necessary to complete tasks that involved ethical issues.…”
Section: Trust and Distrust In Personnel Selection Contextmentioning
confidence: 99%
See 2 more Smart Citations